Dietary-driven variation effects on the symbiotic flagellate protists communities of the subterranean termite Reticulitermes grassei Clément - Duarte, Sónia (2018)
The ability of subterranean termites to digest lignocellulose relies not only on their digestive tract physiology, but also on the symbiotic relationships established with flagellate protists and bacteria. The objective of this work was to test the possible effect of different cellulose-based diets on the community structure (species richness and other diversity metrics) of the flagellate protists of the subterranean termite Reticulitermes grassei. Termites belonging to the same colony were subjected to six different diets (natural diet, maritime pine wood, European beech, thermally modified European beech, cellulose powder and starvation), and their flagellate protist community was evaluated after the trials. All non-treated sound woods produced similar flagellate protist communities that were more diverse and of high evenness (low dominance). On the contrary, flagellate protist communities from cellulose-fed termites and starving termites were considered to be significantly different from all non-treated woods; they were less diverse and some morphotypes became dominant as a consequence of flagellate protist communities having suffered major adaptations to these diets. The flagellate protist communities of untreated beech and thermally modified beech-fed termites were considered to be significantly different in terms of abundance and morphotype diversity. This may be caused by a decrease in lignocellulose quality available for termites and from an interference of thermally treated wood with the chemical stability of the termite hindgut. Our study suggests that as a consequence of the strong division of labour among these protists to accomplish the intricate process of lignocellulose digestion, termite symbiotic flagellate protist communities are a dynamic assemblage able to adapt to different conditions and diets. This study is important for the community-level alteration approach, and it is the first study to investigate the effects of thermally modified wood on the flagellate protist communities of subterranean termites.